2018
DOI: 10.1007/s40520-018-0918-9
|View full text |Cite
|
Sign up to set email alerts
|

Educational strategies to train health care professionals across the education continuum on the process of frailty prevention and frailty management: a systematic review

Abstract: BackgroundIn addition to the normal process of ageing, frailty, defined as a geriatric syndrome, is becoming more prevalent. Around 10% of people over 65 years and 25–50% of those aged over 85 years are frail. Frail elderly are more vulnerable to external stressors and have an increased risk of adverse health outcomes. To tackle these challenges, European Union (EU) member states need to develop a health work force capable of the right skills mix. A goal-centred education and training of professionals is cruci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 20 publications
(17 reference statements)
0
35
0
Order By: Relevance
“…A recent systematic review that involved searches until May 2017 found no relevant article on education and/or training interventions for health care professionals in the field of frailty. 100 There are currently ongoing frailty projects including educational components targeting health care professionals, patients, and caregivers, and new findings from these projects are expected to contribute to the field of frailty. 14,100 There is an increasing interest in frailty in other medical fields than the geriatrics.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A recent systematic review that involved searches until May 2017 found no relevant article on education and/or training interventions for health care professionals in the field of frailty. 100 There are currently ongoing frailty projects including educational components targeting health care professionals, patients, and caregivers, and new findings from these projects are expected to contribute to the field of frailty. 14,100 There is an increasing interest in frailty in other medical fields than the geriatrics.…”
mentioning
confidence: 99%
“…100 There are currently ongoing frailty projects including educational components targeting health care professionals, patients, and caregivers, and new findings from these projects are expected to contribute to the field of frailty. 14,100 There is an increasing interest in frailty in other medical fields than the geriatrics. 101,102 One example is that frailty has recently been pursued as a potential risk assessment measure for older surgical patients and has shown to be promising in predicting post-operative complications, such as mortality or length of hospital stay.…”
mentioning
confidence: 99%
“…Task 8.1 (WP8) was asked to critically appraise the current evidence in the field of education/training for health professionals in the prevention of frailty across the European member states. The consortium showed the absence of evidence for the benefit of educational interventions of staff involved into the care process [3].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the European Commission (EC) has prioritized frailty within the health policy agenda of the majority of the European Union (EU) member states through its "Joint Action on Frailty Prevention" (ADVANTAGE JA) consortium [2]. Despite the absence of evidence supporting education and training programs for professionals involved within the care pathway for older people [3], the consortium assumed that a common competency framework for different professions would support interprofessional collaborative practice (ICP) for integrated and high-quality care for older people [4]. ICP differs from inter-or multi-professional collaboration in terms of hierarchy, role clarification of team members, responsibilities within the team, communication structures and interactions with patients and relatives.…”
Section: Introductionmentioning
confidence: 99%
“…However, a gap in educational research was identified in a recent systematic review, where to date, there has been no research describing the effectiveness of educational programs specifically related to frailty. 11 The aim of this study was to investigate the perceptions of fifth-year medical students, before and after attending a geriatric medicine course, in relation to their perceived competence in assessing, diagnosing and managing frailty, and how important the topic of frailty is to their medical knowledge.…”
Section: Introductionmentioning
confidence: 99%